Comparative Effectiveness and Functional Outcome of C2 Dome-like Expansive Versus C2 Expansive Open-door Laminoplasty for Upper Cervical Ossification of the Posterior Longitudinal Ligament: A Retrospective Cohort Study. Issue 10 (15th May 2022) - Yu, Chengcheng; Wu, Yinan; Zhang, Zengjie; Zhang, Ning; Yu, Xinning; Li, Fangcai; Chen, Weishan; Chen, Qixin; Li, Wanli
Abstract : This study performed an analysis of C2 dome-like expansive laminoplasty (Group Dom) and C2-7 expansive open-door laminoplasty (Group Exp). The space available for cord in Group Exp was significantly larger than Group Dom, while the visual analog scale score of Group Dom became significantly larger. Abstract : Study Design: Retrospective Cohort Study. Objectives: This study compared the function and radiographical outcomes of the patients who underwent C2 dome-like expansive laminoplasty to those C2 expansive open-door laminoplasty for the treatment of OPLL with C2 involved. Summary of Background Data: There are few comparative studies of these two surgical methods. C2 dome-like and C2 expansive open-door laminoplasty are posterior approaches for posterior longitudinal ligament ossification with C2 level and above. Methods: This study performed a retrospective cohort analysis of 59 patients with OPLL up to C2 which cause compression symptoms. 31 patients underwent C2 dome-like expansive laminoplasty with C3-7 expansive open-door laminoplasty (Group Dom) and 28 underwent C2-7 expansive open-door laminoplasty (Group Exp). The preoperative and postoperative space available for cord (SAC) of C2 segment, cervical curvature index of C2-7, C2-7 range of motion, Japanese orthopedic association (JOA) score, visual analog scale (VAS) score, and neck disability index (NDI) were used to assess clinical out-comes and statistically analyzed. Results: The cervical curvature index, JOA score, and NDI significantly changed at the final follow-up in two groups with no significant intergroup differences. There were no significant differences in preoperative SAC and VAS between the two groups. At the final follow-up, the SAC of C2/3 in Group Exp was significantly larger than Group Dom, while the VAS and range of motion of Group Dom became significantly better than Group Exp. Conclusion: The C2 dome-like expansive laminoplasty can reduce postoperative neck pain more obviously and achieve better cervical curvature. C2 expansive open-door laminoplasty can get more adequate decompression in the spinal canal, which may be recommend to the patients with OPLL occupying more than 50% of the vertebral canal at C2/3, or with developmental spinal stenosis. Level of Evidence: 3